Determination of the reflectivity of crystals by ptychography - Kai S. Schulze (AIP Advances, 2022)
The x-ray reflectivity of crystals is an important measure for their quality. Its knowledge is of interest for the development of materials as well as for the design of x-ray optical instruments, while the determination of the reflectivity curve is not trivial. This article presents an approach to retrieve the reflectivity curve of crystals based on ptychography. The method is demonstrated on the examples of silicon and diamond of which the reconstructed reflectivity curves agree well with theoretical expectations. Thus, this method offers promising perspectives in the detection of small crystalline defects and in the design of future instruments for x rays.